2010
DOI: 10.1111/j.1759-5436.2010.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Voices, Work and Bodily Integrity in Pre-Conflict, Conflict and Post-Conflict Reconstruction Processes in Sierra Leone

Abstract: This article focuses on the historical trajectories of women's empowerment in Sierra Leone, taking three entry-points as a means of exploring the dynamics of change over the pre-conflict, conflict and postconflict periods: voice and political participation; work and economic participation; and bodily integrity. Looking at pathways of empowerment in pre-conflict Sierra Leone, at experiences of women during the time of conflict over the course of a long and brutal civil war from 1991-2002, and at post-conflict p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Inconsistent condom use within conflict-affected settings was commonly elucidated as a consequence of reduced negotiating power due to financial constraints during times of social unrest [ 30 , 36 , 39 , 40 ]. Conflict-affected sex workers in sub-Saharan Africa commonly supported dependent children [ 14 , 42 ], and having children (especially young children) was associated with increased HIV risks including engaging in unprotected sex for more money [ 14 ]. Although further research is needed in this area, two studies suggested increased need/opportunity to charge extra money for unprotected intercourse during or following a crisis [ 43 , 44 ], including a study of Kenya’s 2008 post-election violence on sex workers and their clients, where dramatic declines in income, expenditures, and consumption in the general population resulted in more unprotected sex [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent condom use within conflict-affected settings was commonly elucidated as a consequence of reduced negotiating power due to financial constraints during times of social unrest [ 30 , 36 , 39 , 40 ]. Conflict-affected sex workers in sub-Saharan Africa commonly supported dependent children [ 14 , 42 ], and having children (especially young children) was associated with increased HIV risks including engaging in unprotected sex for more money [ 14 ]. Although further research is needed in this area, two studies suggested increased need/opportunity to charge extra money for unprotected intercourse during or following a crisis [ 43 , 44 ], including a study of Kenya’s 2008 post-election violence on sex workers and their clients, where dramatic declines in income, expenditures, and consumption in the general population resulted in more unprotected sex [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…This form of trade takes place in both local and urban areas of the African countries (Hamat, Malek, Leng, Gopal and Husain, 2014). Although men are equally engaged in petty trading (Amrevurayire and Ojeh, 2016), rural women are mostly found engaging in petty trading (Abdullah, Ibrahim and King, 2010). Children petty traders or hawkers are frowned at, as it is being seen as child labour (Ampomah, 2012).…”
Section: Petty Tradingmentioning
confidence: 99%
“…It is lamentable that in a situation where women are relatively well empowered to participate in formal politics as a result of their participation during the war (Abdullah, Ibrahim, & King, 2010), they remain excluded by the fact that informal politics, and surrounding corruption issues, are so significant in decision making.…”
Section: Corruption and Policingmentioning
confidence: 99%
“…While women in Sierra Leone have an active political and social voice (Abdullah et al, 2010) the time commitment of caring for children and limitations on where it is safe for them to travel alone in the evenings, can act to limit or exclude their participation in public fora. By being able to send a groupappointed representative to FUPAAP, the women are able to ensure that their views are accurately represented without having to take time away from their family or fields.…”
Section: Fupaap; Establishments and Benefitsmentioning
confidence: 99%